Ding Dong Gorilla! - Robinson, Michelle; Illustrated by Lord, Leonie (London Orchard Books, 2013)
DING DONG! When a gorilla pays a visit, it's not long before mischief and mayhem ensue!
Includes Color IIlustrations
Keywords: Children's Stories -- Toy Box